New Antimicrobials Based on the Adarotene Scaffold with Activity against Multi-Drug Resistant Staphylococcus aureus and Vancomycin-Resistant Enterococcus - Salvatore Princiotto; Stefania Mazzini; Loana Musso; Fabio Arena; Sabrina Dallavalle; Claudio Pisano (MDPI AG, 2021)
The global increase in infections by multi-drug resistant (MDR) pathogens is severely impacting our ability to successfully treat common infections. Herein, we report the antibacterial activity against S. aureus and E. faecalis (including some MDR strains) of a panel of adarotene-related synthetic retinoids. In many cases, these compounds showed, together with favorable MICs, a detectable bactericidal effect. We found that the pattern of substitution on adarotene could be modulated to obtain selectivity for antibacterial over the known anticancer activity of these compounds. NMR experiments allowed us to define the interaction between adarotene and a model of microorganism membrane. Biological assessment confirmed that the scaffold of adarotene is promising for further developments of non-toxic antimicrobials active on MDR strains.